2008
DOI: 10.1097/01.pcc.0000298642.11872.29
|View full text |Cite
|
Sign up to set email alerts
|

Do outcomes vary according to the source of admission to the pediatric intensive care unit?*

Abstract: Outcomes of tertiary pediatric intensive care vary significantly by source of admission. Strategies aimed at reduction of mortality at the tertiary PICU should target transfer admissions from the hospital's wards and from PICUs of other hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 31 publications
10
97
1
6
Order By: Relevance
“…In another single-center study in the United States, Odetola et al 10 found a higher risk of mortality in patients transferred from acute care units than in patients transferred from the emergency department. In a tertiary care PICU in Brazil, mortality was twice as high in patients admitted from acute care units compared with patients admitted from the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…In another single-center study in the United States, Odetola et al 10 found a higher risk of mortality in patients transferred from acute care units than in patients transferred from the emergency department. In a tertiary care PICU in Brazil, mortality was twice as high in patients admitted from acute care units compared with patients admitted from the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…7 Converted to cyanide by erythrocyte and tissue sulfhydryl group interactions; cyanide is converted in the liver by the enzyme rhodanase to thiocyanate (thiocyanate levels should be monitored). 8 Metabolized in the liver; Causes thrombocytopenia (may be dose-related); Milrinone is now preferred agent 9 Metabolized in the kidney; Relatively long half-life (use with caution in children with hemodynamic instability) 10 Dose may be decreased once the ductusarteriosus has opened with very little change in therapeutic effects; may cause hypotension, apnea, cutaneous flushing should be secured as rapidly as possible, followed by volume resuscitation with isotonic saline or colloid fluid boluses of 20 mL/kg every 5 minutes to a total of 60 mL/kg [29,30]. Antibiotics should be administered to children with suspected sepsis within the first 15 minutes of shock management.…”
Section: Initial Resuscitation Phasementioning
confidence: 99%
“…However, early management is critically dependent upon the early recognition and diagnosis of shock at the bedside. Failure to recognize the signs and symptoms of shock and to institute timely and appropriate care leads to higher mortality rates in both children and adults [7][8][9][10][11]. Clinical recognition of shock requires a high index of suspicion -as such, all pediatric health care providers should be cognizant of the clinical presentation, pathophysiology, and early management of shock.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of interhospital ICU to ICU transfers have focused mainly on the methods of transport, the obligatory preparations, frequency of transport-related adverse events, [13][14][15][16][17] and outcome and resource comparisons among transfer sources (ICU, emergency department, and general care unit). [3][4][5][18][19][20][21] ally performed at MSKCC, any associated complication, and the timing of the intervention in relation to the transfer were determined. If a planned intervention was not performed, medical records were consulted to determine the reason for deferral.…”
Section: Data Source and Study Settingmentioning
confidence: 99%